ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI TERAPI MUROTTAL QURAN TERHADAP INTENSITAS NYERI PADA IBU POST SECTIO CAESAREA DENGAN INDIKASI PREEKLAMSIA DI RSUD PASAR MINGGU - Jihan Almira Dewi (2023)
Childbirth is a psychological, social and emotional experience that can be directly related to the physiological and psychological conditions of the mother after giving birth. One of the delivery procedures is cesarean section. Caesarean section is included in a surgical procedure that can only be performed based on indications of certain health problems that can cause injuries to the mother's abdomen with the aim of expelling the fetus. The purpose of this study was to analyze the intervention of murottal Quran therapy for pain caused by an incision in the abdomen after cesarean section surgery. This study used a quasi-experimental research design on two post-cesarean section patients with indications of preeclampsia with pain intensity measured by the Numeric Rating Scale (NRS) which consisted of a scale of 0 (no pain) to a scale of 10 (very severe pain). The results of this study showed that the scale of pain intensity in both patients was reduced after three days of intervention with murottal Quran therapy. The first patient on the first day, a scale of 7 was obtained (severe pain) and on the third day of intervention it became a scale of 4 (moderate pain) and the other patient got a scale of 6 (moderate pain) and on the third day of intervention it became a scale of 3 (mild pain). It is recommended for post-cesarean section mothers who experience pain and are Muslim to use this murottal Quran therapy as a non-pharmacological therapy that can help reduce pain intensity.